SOCIALIZATION OF REGIONAL REGULATION NO. 11 OF 2017 REGARDING EMBANKMENTS IN THE SARI BARUNA FISHERMEN'S GROUP OF BANJAR KHUBUR, KETEWEL VILLAGE, GIANYAR - I Wayan Novy Purwanto; I Gusti Ayu Putri Kartika; I Nyoman Bagiastra; Ayu Putu Laksmi Danyati; Dewa Gede Pradnyana Yustiawan (Transpublika Publisher, 2024)
The purpose of this socialization is to educate and inform the Sari Baruna Fishermen Group of Banjar Khubur Ketewel Village, Gianyar about Regional Regulation Number 11 of 2017 regarding Bendega. It is crucial for the fishermen to understand this regulation as it addresses the problems they face. The Regional Government is committed to preserving and protecting Bendega, which is an integral part of Balinese culture. By safeguarding the ethical, moral, and civilizational values of Balinese customs, the government ensures the continuity of these traditions. Bendega holds significant economic, social, cultural, and religious importance in the indigenous communities of Bali's coastal areas. To protect and preserve Bendega, various strategies are implemented, including the continuous application of Tri Hita Karana principles, enhancing the skills and knowledge of Bendega personnel, and empowering Bendega through economic activities rooted in local wisdom. Additionally, the strengthening of Bendega institutions and financial support are provided. It is essential to socialize these efforts to the fishermen groups so that they can fully comprehend the protection offered by the Regional Government. This understanding will enable the fishermen to exercise their rights and responsibilities as coastal fishermen.